2022
DOI: 10.1007/s44197-022-00049-1
|View full text |Cite
|
Sign up to set email alerts
|

The Global Epidemiological Transition in Cardiovascular Diseases: Unrecognised Impact of Endemic Infections on Peripheral Artery Disease

Abstract: An epidemiological transition in the prevalence of peripheral artery disease (PAD) is taking place especially in low- and middle-income countries (LMICs) where an ageing population and adoption of western lifestyles are associated with an increase in PAD. We discuss the limited evidence which suggests that infection, potentially mediated by inflammation, may be a risk factor for PAD, and show by means of an ecological analysis that country-level prevalence of the major endemic infections of HIV, tuberculosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Preliminary ecological evidence shows an association between PAD prevalence and country‐level burdens of endemic infectious diseases like HIV, tuberculosis, and malaria. 40 Historically, rural South Africa has had a high infectious disease burden, including HIV. Approximately 23% of the HAALSI population is HIV‐positive with South Africa having one of the highest HIV burdens globally.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary ecological evidence shows an association between PAD prevalence and country‐level burdens of endemic infectious diseases like HIV, tuberculosis, and malaria. 40 Historically, rural South Africa has had a high infectious disease burden, including HIV. Approximately 23% of the HAALSI population is HIV‐positive with South Africa having one of the highest HIV burdens globally.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative potential risk factors for PAD in this population include endemic infectious diseases, chronic stress, and air pollution. Preliminary ecological evidence shows an association between PAD prevalence and country-level burdens of endemic infectious diseases like HIV, tuberculosis, and malaria 40 . Historically, rural South Africa has had a high infectious disease burden, including HIV.…”
Section: Discussionmentioning
confidence: 99%
“…By the rate of prevalence, stroke, and Peripheral arterial disease are Indonesia's two most common CVDs. PAD is frequently neglected, a study of ankle-brachial index examinations in diabetes mellitus patients in Indonesia revealed that 14.5% had lower extremity PAD [20][21][22]. Another study reported that as many as 42% of chronic kidney disease patients had moderate Ankle Brachial Index (ABI) results.…”
Section: Indonesia Pattern In Global Burden Diseasementioning
confidence: 99%